The dentate gyrus provides flexibility for efficient spatial navigation - Soldi, Natalia (2024)
The hippocampus plays a critical role in spatial navigation and declarative memory. The dentate gyrus is the neurogenic region of the hippocampal formation and it has long been implicated in the fine separation of similar contexts or close object locations. However, it is unclear how an accurate discrimination could be beneficial to a goal-guided behavior in a changing environment. Therefore, we used chemogenetic inhibition to study the role of the dentate gyrus in a goal-guided spatial navigation paradigm over a familiar but dynamic crossword maze. Mice were challenged to localize a novel reward location from alternative pathways in two versions of the task with particular configurations in each experimental day. In the simple task, the two optimal paths to the goal shared some segments in their trajectory. In a more complex task, optimal trajectories demanded completely different directions to the reward location. Overall, mice with chemogenetic inhibition of the dentate gyrus were able to learn all the routes regardless the complexity of the task, similarly to control animals. However, after having solved a first route in the complex task, mice with dentate gyrus inhibition displayed an impairment to efficiently navigate over the alternate path. Our results demonstrate a role of the dentate gyrus in cognitive flexibility required to reach a goal in a changing familiar environment.